2016
DOI: 10.3348/kjr.2016.17.5.581
|View full text |Cite
|
Sign up to set email alerts
|

Population-Stratified Analysis of Bone Mineral Density Distribution in Cervical and Lumbar Vertebrae of Chinese from Quantitative Computed Tomography

Abstract: ObjectiveTo investigate the bone mineral density (BMD) of cervical vertebrae in a population-stratified manner and correlate with that of the lumbar vertebrae.Materials and MethodsFive hundred and ninety-eight healthy volunteers (254 males, 344 females), ranging from 20 to 64 years of age, were recruited for volumetric BMD (vBMD) measurements by quantitative computed tomography. Basic information (age, height, weight, waistline, and hipline), and vBMD of the cervical and lumbar vertebrae (C2–7 and L2–4) were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 47 publications
4
31
0
Order By: Relevance
“…One cohort comprised of 344 healthy women and was recruited from an ongoing study that has been running since June 2014. This ongoing study examined the degeneration of the spine and knee, described previously (22). The second cohort comprised of one hundred and seventy-two women from the Prospective Urban Rural Epidemiology (PURE) China Action on Spine and Hip status (CASH) study (23,24).…”
Section: Subjectsmentioning
confidence: 99%
“…One cohort comprised of 344 healthy women and was recruited from an ongoing study that has been running since June 2014. This ongoing study examined the degeneration of the spine and knee, described previously (22). The second cohort comprised of one hundred and seventy-two women from the Prospective Urban Rural Epidemiology (PURE) China Action on Spine and Hip status (CASH) study (23,24).…”
Section: Subjectsmentioning
confidence: 99%
“…[24,25] A study showed that BMD values from cervical and lumber spine decreases with aging and degeneration, notwithstanding, the BMD cervical vertebrae of women has increased throughout aging and declined abruptly with menopause. [26] These findings show that the cervical vertebrae may present higher BMD values comparing with lumbar vertebrae. Women before menopausal and postmenopausal can present different values of BMD in cervical spine in contrast to men.…”
Section: Discussionmentioning
confidence: 63%
“…Women before menopausal and postmenopausal can present different values of BMD in cervical spine in contrast to men. [26] This study has several limitations, variations such as its retrospective nature and the small sample size. Another important fact is the variation between ROI positions due to authors and anatomical variation of patients.…”
Section: Discussionmentioning
confidence: 95%
“…This could explain the relationship between IVRO and exhibition of SAP. Furthermore, the decrease in the cancellous bone density of the cervical vertebrae 24 after orthognathic surgery can be considered as evidence of the presence of SAP. Therefore, SAP induced by IVRO can contribute to accelerated postsurgical orthodontic tooth movement.…”
Section: Discussionmentioning
confidence: 99%